2021
DOI: 10.1007/s00412-021-00751-2
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Y pericentric heterochromatin is a primary target of HSF1 in male cells

Abstract: The heat shock factor 1 (HSF1)-dependent transcriptional activation of human pericentric heterochromatin in heat-shocked cells is the most striking example of transcriptional activation of heterochromatin. Until now, pericentric heterochromatin of chromosome 9 has been identified as the primary target of HSF1, in both normal and tumor heat-shocked cells. Transcriptional awakening of this large genomic region results in the nuclear accumulation of satellite III (SATIII) noncoding RNAs (ncRNAs) and the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…One of the most striking effects of stress is the rapid and reversible redistribution of HSF1 into a few nuclear structures termed nuclear stress granules which form primarily on the 9q12 locus and chromosome Y [50] and secondary on several other chromosomes (including chromosome 1) enriched in SatII and SatIII sequences in humans. Within these structures, HSF1 binds to satellite II and III repeated elements at several pericentromeric regions in heat-shocked cells [51] and drives the transcription of these sequences into stable RNAs which remain associated with the source DNA locus for a certain time after synthesis.…”
Section: Generic Stress Response: What We Learnt Recentlymentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most striking effects of stress is the rapid and reversible redistribution of HSF1 into a few nuclear structures termed nuclear stress granules which form primarily on the 9q12 locus and chromosome Y [50] and secondary on several other chromosomes (including chromosome 1) enriched in SatII and SatIII sequences in humans. Within these structures, HSF1 binds to satellite II and III repeated elements at several pericentromeric regions in heat-shocked cells [51] and drives the transcription of these sequences into stable RNAs which remain associated with the source DNA locus for a certain time after synthesis.…”
Section: Generic Stress Response: What We Learnt Recentlymentioning
confidence: 99%
“…Open chromatin conformation necessary for transcription strongly assists in changing the copy numbers of satellite DNA due to unequal exchanges. Although the stressinduced satellite III DNA transcription with the formation of nSBs occurs primarily on chromosomes 9 [71] and Y [50], chromosome 1 satellite III DNA has been also shown to be decondensed, demethylated and transcribed in senescent cells and in A431 epithelial carcinoma cells [72].…”
Section: Satii/iii Copy Gain In Stress Senescence and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Histone H3 mutations have been found to play a role in a variety of cancers, such as paediatric brain tumors [22]. Penin et al reported that pericentric heterochromatin of chromosome 9 was the primary target of HSF1 in both normal and tumor heat-shocked cells [23]. Zheng et al found that LINC00174 promotes the metastasis and growth of OS through upregulating slingshot protein phosphatase 2 expression [24].…”
Section: Discussionmentioning
confidence: 99%
“…A stress cascade involves the rapid and reversible relocation of HSF1 and some other proteins, particularly splicing factors [ 13 ], into so-called nuclear stress granules. They appear, first of all, on the 9q12 locus and chromosome Y [ 61 ] and, secondarily, on some other chromosomes carrying SatII/III sequences. Within these structures, HSF1 binds to SatII/III repeats at several pericentromeric regions [ 62 ] and launches the transcription of satellite sequences by adding polymerase II to stable transcripts.…”
Section: The Role Of Satellite Repeat Abundance In Modulating Stress ...mentioning
confidence: 99%